Executive Function and Postural Instability in People with Parkinson’s Disease - Dong Xu; Michael H. Cole; Kerrie Mengersen; Peter A. Silburn; Feng Qiu; Cara Graepel; Graham K. Kerr (Parkinson's Disease)
The specific aspects of cognition contributing to balance and gait have not been clarified in people with Parkinson’s disease (PD). Twenty PD participants and twenty age- and gender-matched healthy controls were assessed on cognition and clinical mobility tests. General cognition was assessed with the Mini Mental State Exam and Addenbrooke’s Cognitive Exam. Executive function was evaluated using the Trail Making Tests (TMT-A and TMT-B) and a computerized cognitive battery which included a series of choice reaction time (CRT) tests. Clinical gait and balance measures included the Tinetti, Timed Up & Go, Berg Balance, and Functional Reach tests. PD participants performed significantly worse than the controls on the tests of cognitive and executive function, balance, and gait. PD participants took longer on Trail Making Tests, CRT-Location, and CRT-Colour (inhibition response). Furthermore, executive function, particularly longer times on CRT-Distracter and greater errors on the TMT-B, was associated with worse balance and gait performance in the PD group. Measures of general cognition were not associated with balance and gait measures in either group. For PD participants, attention and executive function were impaired. Components of executive function, particularly those involving inhibition response and distracters, were associated with poorer balance and gait performance in PD.